Academic Misconduct in Higher Education - Al-Sarraf, Mrs. Hanan Hassan (Arab Journal for Sciences and Research Publishing, 2017)
This paper discussed the academic misconduct upon previous research papers. A descriptive deign used to collectdata from studies done in regions all over the world, including Europe, East Asia, and Sub-Saharan Africa. Prevalence ofacademic misconduct and how students engage in misconduct in universities and colleges, and strategies to overcomeacademic misconduct were discussed. In the future direction section, an emphasis is made on the unique challengeacademic misconduct presents in the online environment. Lastly, its recommended to apply multi-faceted approach inaddressing academic misconduct since no single strategy has been found to be effective.
Keywords: misconduct; Higher education; Academic